PENANAMAN NILAI NILAI KEAGAMAAN ORANG TUA SEBAGAI BURUH PABRIK (ERATEK DJAJA) DALAM MENDIDIK ANAK (Study Kasus Para Buruh Pabrik di Kelurahan Sumbertaman Kota Probolinggo) - Zainab, Zainab; Khoiriyah, Khoiriyah (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
This research is a descriptive qualitative method with the background of the residents of Mantong Village, Sumbertaman Village, Wonoasih Subdistrict, Probolinggo City with respondents who work as factory workers in Eratex Djaya. Data collection is done by in-depth interviews, observation, and documentation. The results of this study indicate: (1) The implementation of Islamic Education for children in families who work as Eratex Djaya factory workers is influenced by several factors, namely limited time, background knowledge of parents about Islamic religious education, the level of readiness and intelligence of children, and patterns foster care used by parents. (2) The method applied by parents to Islamic education for their children uses several methods including: a) the exemplary method, b) the habituation method. c) Dialogue method d) Penalty method. (3) Problems faced by parents come from two factors, namely a) Internal, namely limited time, and the level of parental education, b) External, namely environmental factors, and mass media / technology.